Mucoepidermoid Carcinoma of Palatal Minor Salivary Glands with Intracranial Extension: A Case Report and Literature Review - Dossani, Rimal Hanif; Akbarian-Tefaghi, Hesam; Lemonnier, Lori; Mehta, Vikas; Jacobsohn, Jamie A.; Guthikonda, Bharat (Journal of Neurological Surgery Reports, 2016)
Mucoepidermoid carcinoma (MEC) is one of the most common malignant tumors of both major and minor salivary glands. Although there are reports of parotid MEC tumors extending intracranially via the facial nerve, intracranial extension from MEC originating from minor salivary glands in the palate has not previously been reported. This report presents a case of MEC arising from the minor salivary glands of the palate and extending into the middle fossa via the foramen rotundum with perineural invasion of the maxillary division of the trigeminal nerve. The patient received surgical intervention via a combined otolaryngology and neurosurgery approach to achieve gross total resection of the tumor. This was followed by adjuvant radiotherapy. The epidemiology, histopathology, and treatment of MEC originating from salivary glands are discussed.
Keywords: mucoepidermoid carcinoma; intracranial extension; trigeminal nerve; perineural invasion